2016
DOI: 10.1097/brs.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Radiological Severity of Lumbar Spinal Stenosis and Disability, Pain, or Surgical Outcome?

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
0
42
0
7
Order By: Relevance
“…Management of spinal stenosis can be challenging and requires the integration of individual symptoms, clinical findings, and diagnostic imaging. A recent study showed that, in individuals undergoing decompressive surgery for LSS, there was no association between severity of stenosis on preoperative magnetic resonance imaging and preoperative disability or clinical outcomes . This puts further emphasis on medical history taking and clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of spinal stenosis can be challenging and requires the integration of individual symptoms, clinical findings, and diagnostic imaging. A recent study showed that, in individuals undergoing decompressive surgery for LSS, there was no association between severity of stenosis on preoperative magnetic resonance imaging and preoperative disability or clinical outcomes . This puts further emphasis on medical history taking and clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that, in individuals undergoing decompressive surgery for LSS, there was no association between severity of stenosis on preoperative magnetic resonance imaging and preoperative disability or clinical outcomes. 32 This puts further emphasis on medical history taking and clinical investigation. Several clinical signs and symptoms may be present in individuals with symptomatic LSS, including radiating leg pain that is exacerbated by standing or walking and pain relief when seated or bending forward, and many individuals present with gait disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results about the association between radiological and clinical findings. In a multicenter study, no relationship was shown between the radiological severity and the presence of back or leg pain in patients with LSS (23). In another research, the opposite was shown to some extent (24).…”
Section: Resultsmentioning
confidence: 94%
“…Weber et al evaluated the correlation between the severity of stenosis and clinical presentation [21]. They found no clinical correlation between the radiological severity of lumbar spinal stenosis and the nature of the clinical findings, including disability, pain, and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%